Exploiting Britain’s Imperial History: The Polarising Effects of the Culture-War Discourse and the Master Narrative of Nostalgia in Contemporary British Political Rhetoric - Matthias Göhrmann; Dennis Henneböhl (Amnis)
Ever since the Brexit vote of 2016, the term « culture war » has been increasingly employed to describe a fundamental shift in British politics towards a more Americanised and highly divisive political style. This paper will reconceptualise the term - originally popularised in the early 1990s by US sociologist James Davison Hunter – from the perspective of British cultural studies so that it can be productively applied to the British cultural context. Here, the clash between « traditionalist » notions of national identity and « progressivist » ones constitutes a major polarising factor. The paper focuses especially on the polarising debates about British history which resurfaced after the toppling of the statue of slave trader Edward Colston by Black Lives Matter protesters in 2020. Here, the culture-war discourse interrelates with what we call the « master narrative of nostalgia ». This dominant cultural narrative, which was (and is) for instance prominently instrumentalised in the context of Brexit, provides a mainly positive perception of the past, marginalising conflicting views or even omitting them entirely. We will illustrate this process by looking at selected examples of recent rhetorical products from the traditionalist bloc such as speeches or statements made in both traditional and social media.